2018
DOI: 10.3329/bjz.v45i2.35709
|View full text |Cite
|
Sign up to set email alerts
|

Manholes as an important breeding sites for Culex mosquitoes in Gazipur City Corporation, Bangladesh

Abstract: A longitudinal study in under constructing Manholes (considered as mosquito breeding trap of the study area) in a newly constructing road in the ward number 35 was conducted in the post monsoon period of 2016. Four species of mosquito population were available in the stagnant water of temporary breeding sites. Among them Cx. quinquefasciatus was the dominant species (98.6%) followed by Cx. tritaeniorhynchus (0.5%), Ar. subalbatus (0.5%) and Cx. fuscocephala (0.4%). Though the breeding sites were temporary and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Geographically, the mosquito is a cosmopolitan insect with a widespread distribution in the tropical and subtropical regions, and the changes in the environment influence the activity of the insect, which has an impact on its diversity and distribution [ 29 ]. Mosquitoes grow normally at optimum temperatures between 25°C and 27°C.…”
Section: Discussionmentioning
confidence: 99%
“…Geographically, the mosquito is a cosmopolitan insect with a widespread distribution in the tropical and subtropical regions, and the changes in the environment influence the activity of the insect, which has an impact on its diversity and distribution [ 29 ]. Mosquitoes grow normally at optimum temperatures between 25°C and 27°C.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonally, the changing of the environment also affects their activity and impacts on their diversity, distribution, and density. Research has shown that mosquitoes can be competent vectors, efficient distributors, and reinforcing agents for various parasites in animal and human populations [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…vishnui) by the dark brown without pale band of the proboscis and the terga of abdomen was dark with broad white basal bands. 13 Geographically, mosquito is cosmopolite insect, and it widespreads in the tropic and subtropic region, 10 and the changing of the environment will affect the insect activity in which will have an impact on diversity and distribution. 1,4,10…”
Section: Diversitymentioning
confidence: 99%
“…Some mosquitoes are cosmopolitan and live nearby human habitations. 10 In Indonesia, 20 mosquitoes species have been known as filariasis vectors, 8 species of Anopheles spp., 3 species of Culex spp., 6 species of Mansonia spp., one species of Aedes, Armigeres, and Coquillettidea, 1 and some of them have biting behaviour in the night time. 11 The nocturnal active biting of vector could be considered as an intermediary for filariasis transmission.…”
Section: Introductionmentioning
confidence: 99%